Studi Kerusakan Umbi Kentang Akibat Cendawan Patogen Pascapanen pada Beberapa Pasar di Kota Ambon - Samponu, Welmince; Leiwakabessy, Christoffol; Rumahlewang, Wihelmina; Uruilal, Costanza; Talahaturuson, Abraham (Fakultas Pertanian, Universitas Pattimura, 2024)
The study aims to determine the level of damage to potato tubers due to post-harvest pathogenic fungi attacks in several traditional markets in Ambon City. This study is a survey study at the Mardika, Passo, and Rumahtiga markets. The results of the study found one type of post-harvest pathogenic fungus that attacks potato tubers in traditional markets in Ambon City, namely Fusarium spp. which is the cause of dry rot disease in potato tubers. The level of damage to potato tubers due to Fusarium spp. attacks is classified as severe, found in the Mardika market at 70.81% and the Transit Passo market at 60.91%. While in the Rumahtiga market only 31.62% are classified as moderate damage.